Salivary gland hybrid tumour revisited: could they represent high-grade transformation in a low-grade neoplasm? - Hellquist, Henrik; Skalova, Alena; Azadeh, Bahram (Virchows Archiv, 2016)
Salivary gland hybrid tumour, first described in 1996, is a very rare neoplasm for which exact morphological criteria have not been universally agreed upon. In contrast, the concept of high-grade transformation (HGT) in salivary neoplasms has been widely accepted during the last decade, and the number of reported cases is rapidly increasing. A review of the literature revealed 38 cases of hybrid tumour reported in 22 publications. During approximately the same time period, well over 100 cases of HGT in salivary neoplasms have been reported. There are important histological similarities between hybrid tumours and salivary tumours with HGT. In the latter, containing one tumour component of low-grade malignancy and the other of high grade, the two tumour components are not entirely separated and appear to originate in the same area. Virtually, all cases reported as hybrid tumour had no clear lines of demarcation between the two tumour types. We are inclined to suggest that most of the 38 cases of hybrid tumours described in the literature would today better be called tumour with HGT rather than hybrid tumour. The relative proportion of the two components may vary, and the high-grade component is sometimes very small, which emphasises the importance of very generous sampling of the surgical specimen. The molecular genetic mechanisms responsible for HGT, including what used to be called hybrid tumour, remain largely unknown. Abnormalities of a few genes (including p53, C-MYC, cyclin D1, HER-2/neu) have been documented. As insufficient data exist on gene abnormalities in these lesions, conclusions as to whether or not they have a common origin and which mechanisms are involved in transformation cannot be drawn. Due to the small number of cases reported, many of which lack follow-up details; indicators of prognosis of hybrid tumours are not available, but their behaviour seems to be similar to that of tumours with HGT, i.e. an accelerated aggressive course. HGT of salivary gland neoplasms greatly influences macroscopic and microscopic evaluation of the specimen but also, given the high incidence of metastases and morbidity, carries significant treatment implications.
Keywords: stupeň nádoru; nádorová transformace buněk; Adult; senioři nad 80 let; High-grade transformation; Aged, 80 and over; Genes, myc; sekundární malignity; Hybrid tumour; geny myc; Humans; ženské pohlaví; Prognosis; dospělí; Salivary glands; Neoplasms, Second Primary; Female; Aged; mužské pohlaví; Male; Salivary gland neoplasms; Neoplasm Grading; lidé středního věku; prognóza; nádory slinných žláz; Middle Aged; senioři; Cell Transformation, Neoplastic; Dedifferentiation; lidé; Salivary Gland Neoplasms